1973
DOI: 10.1029/jb078i032p07623
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic shear wave birefringence as a test of homogeneous elastic anisotropy

Abstract: Ultrasonic shear wave birefringence is used as a positive indicator of elastic anisotropy. Polarized shear waves are generated by conversion of a compressional P wave to a shear S wave at a free surface (Jamieson and Haskins, 1963). The P-S conversion technique is preferred over the direct use of AC-cut quartz shear wave transducers because the wave amplitudes are considerably greater in the conversion technique. Even though the P/S wave amplitude ratio for the P-S conversion transducers is 1/80, the P wave ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The baraboo quartzite, a Grenville marble, and a plastically deformed granitic boulder -were analyzed according to the Q ellipsoid technique. The measuring apparatus used for determining the elastic velocities is described by Tilmann and Bennett [1973]. In addition, optical petrofabric analyses were performed on the quartzite and marble.…”
Section: Testmentioning
confidence: 99%
“…The baraboo quartzite, a Grenville marble, and a plastically deformed granitic boulder -were analyzed according to the Q ellipsoid technique. The measuring apparatus used for determining the elastic velocities is described by Tilmann and Bennett [1973]. In addition, optical petrofabric analyses were performed on the quartzite and marble.…”
Section: Testmentioning
confidence: 99%
“…From time to time, we have seen a resurgence in interest concerning velocity anisotropy in rocks. In the early 1970s, a number of studies dealing with velocity anisotropy in rocks were reported (e.g., Nur and Simmons, 1969;Christensen and Ramananantoandro, 1971;Gupta, 1973;Tilmann and Bennett, 1973;Todd et al, 1973;Bonner 1974). Most of these studies were on low-porosity crystalline igneous rocks.…”
Section: Introductionmentioning
confidence: 97%
“…The anisotropy of rocks may be caused by: (1) lattice (or crystallographic) preferred orientation (LPO), (2) preferred morphological or shape-preferred orientation of inclusions (SPO) [1,2], (3) preferred orientation of micro-cracks/pores, (4) thin layers of isotropic materials with different elastic properties [3], or (5) the combination of the above mentioned parameters. The anisotropy of mechanical properties also depends on the stress level and on the system of acting forces -uniaxial force, confining pressure, etc.…”
Section: Introductionmentioning
confidence: 99%